Bibliophiles Online – A Few Words about Facebook Groups about Books - Edyta Kosik (Toruńskie Studia Bibliologiczne, 2018)
Internet offers new opportunities of communication and integration for book lovers – giving them the possibility to create a community focused on their main passion – reading. The article characterizes a specific type of these communities – Facebook groups about books. The definition of social media and e-communities was presented. Facebook web site was described and characterized. It was noted that the Internet, and therefore Facebook, is a place where lovers of the written word have the ability to communicate between themselves and to integrate. Then, the article presents one of the ways of communication among book lovers on Facebook – book groups. Based on the analysis of 47 groups, the article try to present its structure (size, access and activity of participants) and study the information published by their members. It was pointed out which of these information is most relevant to their participants. The members of the book groups were characterized as well, based on the surveys  conducted between them. It has been shown, which elements are the most appreciated by their participants and which they consider the biggest flaws, finally what encouraged them to join the communities.